PENGEMBANGAN MODUL BIMBINGAN BELAJAR TENTANG PERILAKU PROKRASTINASI AKADEMIK PADA SISWA KELAS X SMAN 1 CIRANJANG - Laras Melinda Yanti; Teti Sobari; Reza Pahlevi (IKIP Siliwangi, 2023)
The module is one of the printed-based teaching materials regarding a particular subject that is systematically arranged to make it easier for students to learn independently or with the guidance of educators easily and on target. Academic procrastination is an individual's self-regulation inability that causes behavioral tendencies to delay procrastinating in doing and completing school assignments until the next day. The purpose of this research is to know the development process, to know the feasibility according to experts and practitioners, to know student responses and the effectiveness of the tutoring module on academic procrastination behavior. This type of research is research and development using the Borg and Gall model which was adopted by Sugiyono. The participants in this study were media experts, material experts, BK practitioners and students of SMAN 1 Ciranjang consisting of 10 students who were involved in the product trial and 36 students who were involved in the usage trial. The results show that the product that needs to be developed at SMAN 1 Ciranjang is a tutoring module about academic procrastination behavior, the product developed according to media experts is at a percentage of 90.6% with a very decent representation, according to material experts it is at a percentage of 95.2% with a very decent representation and according to BK practitioners the product is at a percentage of 96.9% with a very decent representation, the product developed has a very good response from students and the product developed is effective in reducing the level of student academic procrastination behavior.Keywords: Development, Tutoring Module, Academic Procrastination Behavior